Preliminary Histological Evaluation of the Application of Ozone in the First Days of Orthodontic Force Induction in Animal Model - Faccini, Melissa; Agostini, Felipe; Drieu, Tassio; Campos, Francisco Ubiratan Ferreira de; Garcez, Aguinaldo; Carinhena, Glauber Fabre; Salmeron, Samira; Casaroto, Ana Regina; Valarelli, Fabricio Pinelli; Freitas, Karina Maria Salvatore (European Journal of Dentistry, 2021)
Objectives The aim of the study was to histologically evaluate the effect of ozone therapy on orthodontic force induction in an animal model.Materials and Methods Twenty-four Wistar rats were divided into three groups (n = 8). A NiTi coil spring was installed from the maxillary first molar to the maxillary central incisor. G1 was control and G2/G3 received 1 mL of ozonated gas at concentrations of 10 and 60 µg/mL, in the buccal mucosa above the first molar roots. The animals were euthanized 3 and 5 days after the procedure. Histological sections were obtained, longitudinally of the first molar’ long axis, in the mesiodistal direction. The number of osteoclasts, osteoblasts, blood vessels, polymorphonuclear and mononuclear cells, formation of osteoid tissue and hyaline areas, and root resorption were evaluated with light microscope, in tension and pressure sides. Intergroup comparisons were performed with Kruskal–Wallis, Dunn, and Chi-square tests.Results At 3-days pressure side, a greater number of osteoclasts was observed in ozone groups and greater number of blood vessels and polymorphonuclear cells were observed in G2. On the tension side, there was a significantly greater number of blood vessels, osteoblasts, and mononuclear cells in G2. At 5-days pressure side, there was a significantly greater number of osteoclasts in G2, blood vessels and osteoblasts in the ozone groups, and lesser number of polymorphonuclear cells in G3.Conclusion Ozone therapy increased the number of osteoclasts on the pressure side and osteoblasts on tension side, in 10 µg/mL concentration, demonstrating histological parameters favorable to bone remodeling. The 60 µg/mL ozone concentration accelerated the periodontal ligament reorganization process.
Keywords: orthodontic movement; ozone; orthodontics; ozone therapy